IMAM KHOMEINI: FIGURE OF THE IRAN ISLAMIC REVOLUTION - Firdaus Sutan Mamad (Khazanah: Jurnal Sejarah dan Kebudayaan Islam, 2022)
The Iranian Revolution was a revolution that changed the Iranian government system from a monarchy to an Islamic republic led by Imam Rahullah al-Musawi al-Khomeini. Imam Khomeini is a figure in Iran who is also known as the father of the Iranian Revolution of Fundamentalism. His mindset is heavily influenced by mystical, philosophical, and Sufism based on the Qur'an and Hadith. So from Imam Khomeini's thought, the occurrence of the Islamic revolution in Iran on February 11, 1979 brought changes in Iran itself.